2019
DOI: 10.3390/f10010073
|View full text |Cite
|
Sign up to set email alerts
|

Landscape-Scale Mixtures of Tree Species are More Effective than Stand-Scale Mixtures for Biodiversity of Vascular Plants, Bryophytes and Lichens

Abstract: Tree species diversity can positively affect the multifunctionality of forests. This is why conifer monocultures of Scots pine and Norway spruce, widely promoted in Central Europe since the 18th and 19th century, are currently converted into mixed stands with naturally dominant European beech. Biodiversity is expected to benefit from these mixtures compared to pure conifer stands due to increased abiotic and biotic resource heterogeneity. Evidence for this assumption is, however, largely lacking. Here, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 70 publications
5
25
2
5
Order By: Relevance
“…This fact may also result in lower biodiversity differences among forest management systems and combinations of management systems respectively. However, both for eutrophic and acidic beech forests similar trajectories in understorey development after different scales of natural disturbances (see Kompa & Schmidt, 2003 and in response to tree species composition (Heinrichs et al, 2019) have been observed.…”
Section: Discussionmentioning
confidence: 78%
“…This fact may also result in lower biodiversity differences among forest management systems and combinations of management systems respectively. However, both for eutrophic and acidic beech forests similar trajectories in understorey development after different scales of natural disturbances (see Kompa & Schmidt, 2003 and in response to tree species composition (Heinrichs et al, 2019) have been observed.…”
Section: Discussionmentioning
confidence: 78%
“…It was shown that species associated with Scots pine decrease in mixture with European beech, since the latter strongly determines microclimate (Heinrichs et al 2019). As a result, for example the composition of herbaceous plant species in mixtures of beech and conifers was more similar to pure beech stands than to conifer stands (Heinrichs et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that species associated with Scots pine decrease in mixture with European beech, since the latter strongly determines microclimate (Heinrichs et al 2019). As a result, for example the composition of herbaceous plant species in mixtures of beech and conifers was more similar to pure beech stands than to conifer stands (Heinrichs et al 2019). We assume that similar negative effects on species richness by mixing tree species are unlikely to occur in a similar way in Scots pine-oak mixtures since the light regimes in monocultures of the two species do not differ as much as they do between oak and beech or Scots pine and beech.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations